The study of Japanese spiritual gardens - Othman, Jamilah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2005)
The research has focused a study on the Japanese spiritual gardens that evolved within the Heian, Muromachi, and Momoyama periods. Gardens establishment during the periods is believed to have created for ritual and secular purposes. The spiritual gardens. which are considered significant to the research outputs, involved the Paradise. Zen and Tea gardens. Such gardens design principles, philosophy, and concepts are discussed in order to examine the reasons of each spiritual garden existence. Beside that. The importance of utilising specific landscape elements in Japanese spiritual gardens towards evoking the spiritual sense is part of the study.